Surface modification on polycaprolactone electrospun mesh and human decalcified bone scaffold with synovium‐derived mesenchymal stem cells‐affinity peptide for tissue engineering. Issue 1 (3rd April 2014) - Shao, Zhenxing; Zhang, Xin; Pi, Yanbin; Yin, Ling; Li, La; Chen, Haifeng; Zhou, Chunyan; Ao, Yingfang
Abstract Synovium‐derived mesenchymal stem cells (SMSC) have been studied for over a decade since first being successfully isolated in 2001. These cells demonstrate the most promising therapeutic efficacy for musculoskeletal regeneration of the MSC family, particularly for cartilage regeneration. However, the mobilization and transfer of MSCs to defective or damaged tissues and organs in vivo with high accuracy and efficiency has been a major problem in tissue engineering (TE). In the present study, we identified a seven amino acid peptide sequence [SMSCs‐affinity peptide (LTHPRWP; L7)] through phage display technology that has a high specific affinity to SMSCs. Our analysis suggested that L7 efficiently and specifically interacted with SMSCs without any species specificity. Thereafter, L7 was covalently conjugated onto both polycaprolactone (PCL) electrospun meshes and human decalcified bone scaffolds (hDBSc) to investigate its TE applications. After 24 h coculture with human SMSCs (hSMSCs), L7‐conjugated PCL electrospun meshes had significantly more adherent hSMSCs than the control group, and the cells expanded well. Similar results were obtained using hDBSs. These results suggest that the novel L7 peptide sequence has a high specific affinity to SMSCs. Covalently conjugating this peptide to either artificial polymer material (PCL mesh) or natural material (hDBS) significantly enhances the adhesion of SMSCs. This method is applicable to a wide range of potential SMSC‐based TE applications, particularly to cartilage regeneration, via surface modification on various type of materials. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 318–329, 2015.